Introduction to SAAIR Articles - Favish, Judy (South African Journal of Higher Education, 2016)
The theme for the 2011 forum of the Southern African Association of Institutional Research (SAAIR) was Enhancement . It was designed to provide opportunities for critical self-reflection to institutional researchers, planners, quality assurance professionals and other administrators, as well as academics, on how evidence-based practices can be used to improve the quality of teaching practices and graduate attributes. Papers reporting on: • strategic issues related to enhancement, • evidence-based innovations, • the use of information to promote reflective and responsive practices, • new ways of approaching operational tasks, • investigations or evaluations of interventions at UG or PG levels, • the use of IR/QA/planning to improve the quality of the student experience, and • conceptual papers exploring the relationship between institutional research and quality were specifically invited.